Ruscus Genus: A Rich Source of Bioactive Steroidal Saponins - Masullo, Milena; Pizza, Cosimo; Piacente, Sonia (Planta Medica, 2016)
The genus Ruscus (Asparagaceae family) is native to the Mediterranean, Southern and Western Europe and is represented by perennial, rhizomatous, and evergreen shrubs. Among the approximately seven species spread throughout Europe up to Iran, Ruscus aculeatus L. (butcherʼs broom) is the most widely distributed and appreciated. This review provides an overview of the traditional use of Ruscus spp., the current knowledge of the chemistry of this genus, and the pharmacological studies carried out on Ruscus spp. extracts. The underground parts of Ruscus plants are a source of steroidal saponins that can be classified into two structural classes: the hexacyclic spirostanol saponins and the pentacyclic furostanol saponins. The main aglycones are ruscogenin and neoruscogenin. From the pharmacological point of view, the most studied Ruscus species is undoubtedly R. aculeatus, a very ancient phlebotherapeutic agent. Pharmacological investigations since the discovery of the vasoconstrictive and venotonic properties of ruscogenin and neoruscogenin in the underground parts of R. aculeatus are discussed. Preparations based on Ruscus species are currently used for the treatment of chronic venous insufficiency, varicose veins, haemorrhoids, and orthostatic hypotension. Finally, analytical techniques for the quality control of R. aculeatus extracts are reported.
Keywords: Ruscus genus; Asparagaceae; spirostanol saponins; furostanol saponins; chronic venous insufficiency